New Spatial Paradigm in Scenographic Production with Stagecraft. Analysis through the Mandalorian (Season One) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The potential of digital scenography as an alternative to the traditional physical construction of sets and props has led to its growing adoption in recent years in creative disciplines such as theatre, film, and television. The aim of this research is to explore its application in the film industry through Stagecraft technology, which underpins the production of films and series such as The Mandalorian. The first season of this production has been taken as a case study, as it was a pioneer in the use of this technique, and several scenes have been selected to examine the new spatial paradigm promoted by Stagecraft. A graphic methodology has also been followed in its analysis, in order to investigate the spatial conditions implicit in productions using this technology. In this way, the selected scenes are linked with their graphic analyses, identifying the mechanisms involved in the definition of space. From this, a shift in the spatiality implicit in filming and production is recognised: firstly, in the narrative, inherent to the scenographic space where the action takes place; and secondly, in the outcome on screen, as the final projection and finished product. This represents a transformation in the general scopic framework of traditional film production, reflecting a deliberate emphasis on surface imagery as an alternative to real spatial depth. This positions Stagecraft technology as the most advanced tool in digital set design, with significant future potential.
Keywords: Digital scenography; narrative space; screen space; Stagecraft; The Mandalorian